The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/1535370216642044
|View full text |Cite
|
Sign up to set email alerts
|

Chelidonic acid evokes antidepressant-like effect through the up-regulation of BDNF in forced swimming test

Abstract: Depression is usually accompanied by neuro-inflammatory reactions. Chelidonic acid, in particular, has shown anti-inflammatory effects. The objective of this study was to evaluate the anti-depressant effects of chelidonic acid and to discuss the potential mechanisms of a forced swimming test. Chelidonic acid was administered orally once a day for 14 days. On the 14th day, chelidonic acid resulted in a significant decrease in immobility time during the forced swimming test without alteration of locomotor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Male BALB/c mice (Dae-Han Experimental Animal Center, Daejon, Korea) and STAT6-/-mice (Stock No: 002828|Stat6 -Jackson Laboratory, Bar Harbor, ME, USA) aged 4 weeks old were used in accordance with previous reports [11,12]. Experiments were initiated after at least 1 week to adapt to the laboratory environment.…”
Section: Animalsmentioning
confidence: 99%
“…Male BALB/c mice (Dae-Han Experimental Animal Center, Daejon, Korea) and STAT6-/-mice (Stock No: 002828|Stat6 -Jackson Laboratory, Bar Harbor, ME, USA) aged 4 weeks old were used in accordance with previous reports [11,12]. Experiments were initiated after at least 1 week to adapt to the laboratory environment.…”
Section: Animalsmentioning
confidence: 99%
“…In addition, other studies have shown that BDNF plays an important role in the pathogenesis of severe depression [ 34 , 36 , 37 ]. BDNF is involved in the survival of neurons and the regeneration of dopamine, 5-HT, and cholinergic neurons in the central nervous system, and it is also a molecular marker of synaptic plasticity [ 38 ]. Exogenous BDNF has antidepressant effect in the animal model of depression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dose of chelidonic acid was selected based on previously reported pharmacological activities and also verified by determining the LD50. [3,6,18,19] All the animals were given regular pellet food and free access to water throughout the study. Animals were constantly monitored for signs of toxicity and death.…”
Section: Pathologymentioning
confidence: 99%